Has brain imaging discovered anything new about how the brain works? - Passingham, R; Rowe, J; Sakai, K (2013)
There have now been roughly 130,000 papers on fMRI. While these have clearly contributed to our understanding of the functional anatomy of the human brain, it is less clear that they have changed the way in which we think about the brain. The issue, in other words, is whether they have established new principles about how the brain works. In this paper we offer as an example one new principle, partly to lay down the criteria that are required for establishing a new principle, and partly to encourage others to offer other principles. Our example concerns the flexible flow of information through the cortex that must occur according to the demands of the task or current context. We suggest that this flexibility is achieved by feedback connections from the prefrontal and parietal cortex, and that these include connections to sensory and motor areas. However, the nature of the selective effect differs. The parietal cortex can select both within and across processing streams. By across streams we mean that it can have the same influence on different streams, for example the dorsal and ventral visual systems. However, only the prefrontal cortex can also select between processing streams. The difference between the prefrontal and parietal effects is due to their different positions within the processing hierarchy.